2016
DOI: 10.1159/000456074
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Neoplasms in Myotonic Dystrophy Type 1

Abstract: Background: The most frequent skin features associated with myotonic dystrophy type 1 (DM1) are frontal alopecia and pilomatrixomas. Several reports suggest that the incidence of basal cell carcinoma is increased in DM1. However, two recently published studies examining this topic have contradictory results. Objective: To retrospectively study the incidence of cutaneous tumours in patients with DM1. Methods: The clinical features of 102 Caucasian patients diagnosed with DM1 at Bellvitge Hospital in Barcelona, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
2
10
0
1
Order By: Relevance
“…Two small studies from Italy comparing dermatological findings of DM1 patients with controls showed significantly higher frequencies of pilomatricoma, dysplastic nevi, and melanoma in DM1 patients, but found contradictory results with BCC . Similar results for pilomatricoma were reported in a single Spanish center study using patient medical records . No significant BCC prevalence difference between DM1 patients and controls was noted; however, DM1 patients developed BCC at a younger age than controls.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Two small studies from Italy comparing dermatological findings of DM1 patients with controls showed significantly higher frequencies of pilomatricoma, dysplastic nevi, and melanoma in DM1 patients, but found contradictory results with BCC . Similar results for pilomatricoma were reported in a single Spanish center study using patient medical records . No significant BCC prevalence difference between DM1 patients and controls was noted; however, DM1 patients developed BCC at a younger age than controls.…”
supporting
confidence: 53%
“…19,20 Similar results for pilomatricoma were reported in a single Spanish center study using patient medical records. 21 No significant BCC prevalence difference between DM1 patients and controls was noted; however, DM1 patients developed BCC at a younger age than controls.…”
mentioning
confidence: 86%
“…Another Italian study in which dermatological examinations were conducted in 90 DM1 patients and 103 age‐ and gender‐matched controls found that DM1 patients were more likely to have dysplastic nevi and pilomatricoma . Finally, a Spanish study found an increased risk of pilomatricoma in 102 DM1 patients versus age‐ and gender‐matched controls …”
Section: Introductionmentioning
confidence: 99%
“…2–9 A population-based nested case-control study found a significantly higher BCC risk among DM1 patients than age- and sex-matched controls (HR=5.78, 95% CI 3.36 to 9.92, p<0.0001) 10. Another study found that, BCCs developed at a significantly younger age in patients with DM1 as compared with the general population (51 years vs 66 years, p=0.035) 11. There may also be an association between DM1 other forms of skin cancer.…”
Section: Discussionmentioning
confidence: 99%